Pengaruh Metode Birth Ball Terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif di Praktek Mandiri Bidan (PMB) Fifi Maryoni - Linda Wati; Monarisa Monarisa; Rischa Hamdanesti (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Labor is a natural process and causes pain caused by contractions when the mother is about to give birth. One of the non-pharmacological methods that can be used is the birth ball method, which is a method of using a rubber ball filled with air to reduce back pain during pregnancy and childbirth which is safe to use. The purpose of this study was to determine the effect of this type of research, a quasi-experimental design with a pretest-postets group design, by measuring the intensity of labor pain in the first stage of the active phase before and after being given treatment in the group given the birth ball method. The population of this study were all mothers who gave birth normally at PMB Fifi Maryoni from November 2020 to February 2021, the study sample consisted of 30 people in the treatment group. The intensity of labor pain in the active phase of the first stage was measured and recorded directly on the observation sheet provided. Data analysis was carried out bivariate with computerization using the SPSS program. The statistical test used was T - test dependent with a 95% confidence degree (α = 0.05). The results showed that there was a decrease in the intensity of labor pain in the active phase of the first stage after the birth ball method was used. The results showed that there was an effect of the birth ball method on decreasing the intensity of labor pain in the first stage of the active phase before and after being given the birth ball method with p value = 0.000. It is recommended to PMB Fifi Maryoni to be able to provide the birth ball method as one of the non-pharmacological methods in reducing the intensity of labor pain in the first stage of active labor so that the mother can overcome pain during labor.